2009
DOI: 10.1103/physrevb.80.085308
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxy, stoichiometry, and magnetic properties of Gd-doped EuO films on YSZ (001)

Abstract: We have succeeded in preparing high-quality Gd-doped single-crystalline EuO films. Using Eudistillation-assisted molecular beam epitaxy and a systematic variation in the Gd and oxygen deposition rates, we have been able to observe sustained layer-by-layer epitaxial growth on yttriastabilized cubic zirconia (001). The presence of Gd helps to stabilize the layer-by-layer growth mode. We used soft x-ray absorption spectroscopy at the Eu and Gd M4,5 edges to confirm the absence of Eu 3+ contaminants and to determi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
82
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 28 publications
(61 reference statements)
7
82
0
1
Order By: Relevance
“…A few works already report heteroepitaxy and bulklike magnetization of EuO on MgO, but with EuO film thicknesses above several tens of nanometers. 18,21 A recent study by Swartz et al 20 concludes that ultrathin EuO heteroepitaxy on MgO (001) cannot be obtained with film thicknesses below 2 nm. That study also reports the formation of polycrystalline EuO in the initial monolayer regime without any additional oxygen supply.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A few works already report heteroepitaxy and bulklike magnetization of EuO on MgO, but with EuO film thicknesses above several tens of nanometers. 18,21 A recent study by Swartz et al 20 concludes that ultrathin EuO heteroepitaxy on MgO (001) cannot be obtained with film thicknesses below 2 nm. That study also reports the formation of polycrystalline EuO in the initial monolayer regime without any additional oxygen supply.…”
Section: Introductionmentioning
confidence: 99%
“…The major experimental difficulty relies in synthesizing the metastable oxide EuO in its stoichiometric ferromagnetic phase since off-stoichiometry precludes an epitaxial growth and also reduces ferromagnetic exchange in the ultrathin-film limit, which is, however, essential for efficient spin-filter tunneling. [13][14][15][16][17] In recent years, several growth studies on EuO thin films have been presented, in particular on stoichiometric EuO thin films grown coherently on perfectly lattice-matched yttriastabilized zirconia (YSZ) 14,18 and on different cubic oxides with only a few percent tensile lattice strain. 19,20 The system EuO/MgO (001), however, provides a large compressive lattice mismatch of m = (a MgO − a EuO )/a EuO = −18%.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recent studies of spin-resolved x-ray absorption spectroscopy have shown a spin-split conduction band of about 0.6 eV in its ferromagnetic state, creating a nearly 100% spin polarized electrons close to the conduction band edge. 10 Although the stoichiometric EuO has a Curie temperature (Tc) of 69 K, Tc can be enhanced significantly by pressure, [11][12][13] interfacial strain 14 or electron doping via rare-earth atoms [15][16][17][18][19][20][21][22][23][24] or oxygen vacancies. 15,16,[23][24][25] The integrations of EuO with Si, 18,[23][24][25][26][27] GaAs, 28 and GaN 18 have been successfully demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in films doped with gadolinium, the maximum reported T C varies between 120 K (Ref. 15) and 170 K. 14 Films doped with lanthanum have a maximum reported T C between 118 K (Ref. 1) and 200 K. 10 Likewise, for films doped with iron, the reported T C varies between 88 K and 200 K. 6,7 For Gd-doped films grown in an adsorption-controlled regime, however, the Curie temperatures are consistent and similar, 15,16 conceivably due to a minimized amount of oxygen vacancies realized in this particular growth regime.…”
mentioning
confidence: 99%
“…The interaction between the Eu f-electrons and the dopant electrons enhances the ferromagnetic exchange energy 4,5 and results in an increased T C . To date, this has been accomplished through the use of trivalent cations including iron, [6][7][8] lanthanum, 1,9,10 gadolinium, [11][12][13][14][15][16][17] and holmium. 9 Alternatively, the T C can be increased by deliberately making oxygen-deficient EuO such that the resulting oxygen vacancies donate an electron.…”
mentioning
confidence: 99%